2023
DOI: 10.3390/ijms24097826
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Signaling Modulates miR-452-5p and miR-335-5p Expression to Functionally Decrease Epithelial Ovarian Cancer Progression in Tumor-Initiating Cells

Abstract: Epithelial ovarian cancer (EOC) remains the fifth leading cause of cancer-related death in women worldwide, partly due to the survival of chemoresistant, stem-like tumor-initiating cells (TICs) that promote disease relapse. We previously described a role for the NF-κB pathway in promoting TIC chemoresistance and survival through NF-κB transcription factors (TFs) RelA and RelB, which regulate genes important for the inflammatory response and those associated with cancer, including microRNAs (miRNAs). We hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Moreover, NF-κB p65 increases miR-200b/c expression by binding to its promoter, subsequently sensitizing ovarian cancer cells to cisplatin [ 100 ]. It also regulates the downstream miRNAs miR-452-5p and miR-335-5p through the NF-κB TFs RelA and RelB, preventing the recurrence of OC [ 101 ]. Moreover, the NF-κB signaling pathway has been implicated in immunosuppression and immune evasion in ovarian cancer cells partly via NFκB-dependent production of IL-6, which impairs DCs but generates and recruits immunosuppressive MDSCs, and IL-8, which increases the expression of the immunosuppressive enzyme arginase [ 102 ].…”
Section: Mechanisms Of Drug Resistance In Ovarian Cancermentioning
confidence: 99%
“…Moreover, NF-κB p65 increases miR-200b/c expression by binding to its promoter, subsequently sensitizing ovarian cancer cells to cisplatin [ 100 ]. It also regulates the downstream miRNAs miR-452-5p and miR-335-5p through the NF-κB TFs RelA and RelB, preventing the recurrence of OC [ 101 ]. Moreover, the NF-κB signaling pathway has been implicated in immunosuppression and immune evasion in ovarian cancer cells partly via NFκB-dependent production of IL-6, which impairs DCs but generates and recruits immunosuppressive MDSCs, and IL-8, which increases the expression of the immunosuppressive enzyme arginase [ 102 ].…”
Section: Mechanisms Of Drug Resistance In Ovarian Cancermentioning
confidence: 99%
“…Studies have suggested that the NF-κB signaling pathway plays a critical role in promoting tumor development [14][15][16]. Changes in the TLR4/NF-κB signaling pathway were further investigated following alterations in HMGB1 expression.…”
Section: Hmgb1 Regulated Tlr4/nf-κb Signalingmentioning
confidence: 99%